THE GENERAL GEOLOGY OF AIR PAPAN AREA, EAST JOHOR, PENINSULAR MALAYSIA: EMPHASIS ON FRACTURE PATTERNS AND ITS STRUTURAL IMPLICATION - TIONG, MICHELLE (Universiti Teknologi PETRONAS, 2015)
East Johor is mainly composed of Palaeozoic rock, which is covered by three formations, which are Mersing Formation, the oldest formation, followed by Murau Conglomerate and the youngest Jasin Volcanic at that region. Intense deformation took place in the old days resulted in a variety of fracture systems. By studying the geological structures in eastern Johor, paleo-stress can be analysed with the understanding on structural patterns. Besides, the fracture network of the rocks can be further studied in order to find out its possibility to be one of the fractured reservoir analogues. This study comprises two significant parameters: deformation patterns and impacts of fractures. By conducting a fieldtrip to the study area – Mersing-Endau and having a detail observation at the focal point – Air Papan, required data, such as fracture system measurement, outcrop observation and rock sample collection were acquired. The observed area is highly fractured and composed of two lithologies; they are named as Lapilli Tuff and tuff. The results of XRD reveals that the Lapilli Tuff and tuff are composed of quartz. Their origins are most probably related to the volcanism which is associated with the subduction of Sibumasu underneath the East Malaysia Block (Indochina Blocks) during the Permo-Triassic. A total of 512 fracture readings were measured to study the paleostress field. Four fracture sets were identified, which are N-S (F1), NE-SW (F2), E-W (F3) and WNW-ESE (F4) directions. Most of these fractures are steeply dipping, with the value more than 70°. Fractures formed in Lapilli Tuff, show a quite consistent fracture pattern. They have been analysed and possible conjugate fracture set was interpreted in N-S (F1) and E-W (F3) directions, which possible induced by a NE-SW compression. Similarly, the Penyu Basin, which is approximately 109km to Northeastern Air Papan, comprised of E-W trending half grabens in the western part which is possible to be related to E-W fractures in this region. As an implication, the Air Papan coastline is possible have structural relationship with Penyu Basin, and could be an analogue of fractured basement.